Entropology and the end of nature in Lance Olsen's Theories of Forgetting. Issue 2 (7th February 2019) - Gibbons, Alison
ABSTRACT: In Tristes Tropiques, Lévi-Strauss coins the term 'entropology', a lexical blend of 'entropy' and 'anthropology' signifying that the study of humankind is always, necessarily, the study of humankind's transformative (disruptive, corrosive) impact. This article traces entropology as an aesthetic practice through Robert Smithson's Earthwork, particularly the Spiral Jetty, and into twenty-first century ecoliterature. At the heart of the article is an analysis of Lance Olsen's contemporary fiction Theories of Forgetting, focusing on the interconnected portrayals of human fragility and the environment. Theories of Forgetting embodies entropology both in its material poetics and as a thematic trope. By representing the entropological inseparability of the fates of humankind and the natural world, the novel casts contemporary human life paradoxically as both destructive and vulnerable. These affects subsequently require the characteristically metamodern renewal of historical thinking by bringing into focus the impact of humanity's past and present actions on the future.